Comparative Analysis of Company Financial Performance Before and During the Covid-19 Pandemic on LQ45 Index - Triska Alviana; Megawati Megawati (Financial Management Studies, 2021)
This study discusses the analysis of the company's financial performance before and during the Covid-19 pandemic on the LQ45 company index. The purpose of this study was to determine the significant differences in the financial performance of companies listed on the LQ45 index between before and during the Covid-19 pandemic. This type of research is quantitative research with comparative analysis. The population of this study is the entire index of LQ45 companies listed on the Indonesia Stock Exchange. In this study, the purposing sampling method was used in sampling and obtained a total sample of 34 samples. The data used in this study is secondary data in the form of the company's quarterly financial statements obtained from www.idx.co.id. This study uses Return on Assets, Return on Equity, Earning Per Share, Current Ratio, and Debt to Equity Ratio as the tested financial ratio variables. The analysis technique used is a hypothesis test using SPSS 16. The data analysis method used is descriptive statistics, data normality test, and paired sample t-test. The results of this study indicate that there are differences in profitability ratios before and during the Covid-19 pandemic, there are insignificant differences in liquidity ratios before and during the Covid-19 pandemic, and there are insignificant differences in leverage ratios before and Happy Covid-19 pandemic.